2021
DOI: 10.21203/rs.3.rs-641221/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interdecadal Change in the Effect of Tibetan Plateau Snow Cover on Spring Precipitation over Eastern China around the Early 1990s

Abstract: Previous works extensively investigated the influences of the winter-spring Tibetan Plateau snow cover (TP, TPSC) on climate variability over the East Asia. The present work documents an interdecadal-changed impacts of different spring TPSC anomaly (TPSCA) patterns on spring precipitation over eastern China (SPEC) around the early 1990s. It is found that the correlation of eastern and western TPSCA shifts from negative to positive around 1990. The empirical orthogonal function (EOF) analysis applying onto the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Previous studies revealed that snow cover can be modulated by the above anomalous atmospheric circulation, which could impact snow variation by modulating upward/downward motion as well as water vapor transport (e.g., Jia et al., 2021; Qian et al., 2019; Zhang, Guo & Wen, 2021; Zhang, Jia & Wen, 2021). However, in the current work, we want to emphasize that snow cover could also play a role in the above atmosphere.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Previous studies revealed that snow cover can be modulated by the above anomalous atmospheric circulation, which could impact snow variation by modulating upward/downward motion as well as water vapor transport (e.g., Jia et al., 2021; Qian et al., 2019; Zhang, Guo & Wen, 2021; Zhang, Jia & Wen, 2021). However, in the current work, we want to emphasize that snow cover could also play a role in the above atmosphere.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…More specifically, it has been found that a warm TP leads to above‐normal summer rainfall in the middle and lower reaches of the Yangtze River valley (Ding et al, 2009; Wang et al, 2008; Xu et al, 2013; Zhang et al, 2004). Since the late 1990s, the TP has shown a notable warming trend, which has intensified the East ASM, thus causing a northward migration of the summer rainfall belt in East Asia (Si & Ding, 2013; Zhang et al, 2021). Moreover, several studies have also indicated that the heat source over the TP can cause significant climate fluctuations in other regions in the northern Hemisphere, such as South Asia (Sun et al, 2021; Wu & Zhang, 1998; Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it has been reported that the spring and summer relationship of the precipitation over the southeast China experienced an out‐of‐phase decadal changes in 1990s, which is mainly driven by the warming SST over the Indian Ocean (Ren et al., 2017; Z. Zhu et al., 2014). In the TP regions, an interdecadal shift of the TP snow cover has been found and its impact on the precipitation over the eastern China is increased after the 1990s (C. Zhang et al., 2022; Jia et al., 2021). Meanwhile, C. Zhou et al.…”
Section: Introductionmentioning
confidence: 99%